2013
DOI: 10.1016/j.jvs.2013.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Pathology Determines Midterm Outcome After Endovascular Repair of the Thoracic Aorta. Report from the Medtronic Thoracic Endovascular Registry (MOTHER) Database

Abstract: interval, 2.71-2.81) compared with never smokers. This was despite the fact that 44% of the baseline smokers who responded to the 8-year resurvey had stopped smoking at that point. Mortality was tripled, largely irrespective of age, in those still smoking at the 3-year resurvey (rate ratio, 2.97; 2.88-3.07). The 12-year mortality was doubled (rate ratio, 1.98; 1.91-2.04) even for women smoking fewer than 10 cigarettes daily at baseline. Of the 30 most common causes of death, 23 were increased significantly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
3
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(128 citation statements)
references
References 0 publications
7
115
3
3
Order By: Relevance
“…We can speculate that these dissections are procedure related. In contrast to the MOTHER (Medtronic Thoracic Endovascular Registry) database, 8 which showed that 50% of RTAD occurs after the 30th day after surgery, we did not identify any cases during the follow-up period. The potential factors that predispose patients to RTAD after TEVAR may be classified as procedure related, device related, and aorta related (from aortic wall fragility and aortic morphology).…”
Section: Time Of Diagnosiscontrasting
confidence: 83%
“…We can speculate that these dissections are procedure related. In contrast to the MOTHER (Medtronic Thoracic Endovascular Registry) database, 8 which showed that 50% of RTAD occurs after the 30th day after surgery, we did not identify any cases during the follow-up period. The potential factors that predispose patients to RTAD after TEVAR may be classified as procedure related, device related, and aorta related (from aortic wall fragility and aortic morphology).…”
Section: Time Of Diagnosiscontrasting
confidence: 83%
“…Daten des IRAD-Registers zeigen bessere Überle-bensraten von interventionell versorgten komplizierten Typ-B-Aortendissektionen als bei Patienten, die einer offenen operativen Versorgung zugeführt wurden [44]. Auch bei unkomplizierten Typ-B-Dissektionen, die historisch eher konservativ therapiert wurden, zeigen neueste Daten, dass eine präventive Stentgraftimplantation einen positiven Effekt auf die Komplikationsrate und die 5-Jahres-Überlebens-wahrscheinlichkeit hat [45,46]. Aufgrund der geschilderten Datenlage ist es wahrscheinlich, dass die interventionelle endovaskuläre Stentgraftimplantation eine Indikationserweiterung erfahren wird und sich möglicherweise zum Goldstandard bei anatomisch vertretbaren thorakalen oder thorakoabdominellen Dissektionen entwickeln wird (.…”
Section: Endovaskuläre Behandlungunclassified
“…& Joseph S. Coselli jcoselli@bcm.edu degenerative aneurysms [4][5][6], 16 to 24 % when used for chronic type B aortic dissections [4][5][6][7][8], and 21 to 32 % when used for acute type B dissections [5,6,9,10]. In addition, a lack of operator experience likely plays a role in the development of postoperative complications after TEVAR.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is difficult to assess the rate of open repair after TEVAR, the rates in large series of TEVAR cases ([300) have ranged from 0.4 to 7.9 % [4,6]. Major complications of TEVAR that typically necessitates open distal aortic repair (i.e., repair of the descending thoracic or thoracoabdominal aorta) include endoleak (especially type I), aortic fistula, infection, device collapse or migration, and continued expansion of the aneurysm sac.…”
Section: Introductionmentioning
confidence: 99%